Manajemen Sekolah Adiwiyata Untuk Menumbuhkan Karakter Tanggung Jawab di SD Negeri Magelang 6 Kota Magelang - Abdul Majid; Welius Purbonuswanto (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the implementation of Adiwiyata school management in fostering students' responsibility character, to identify obstacles, and to formulate strategies for overcoming them at SD Negeri Magelang 6, Magelang City. This research used a descriptive qualitative approach with data collection techniques through triangulation, including observation, interviews, and documentation. Data were analyzed interactively through data reduction, presentation, and conclusion drawing. The results showed that the Adiwiyata program was implemented in a structured and participatory manner through planning, implementation, supervision, and evaluation stages. The program involved school principals, teachers, students, school committees, and external partners. Environmental responsibility values were integrated into the curriculum and school culture through activities such as clean-up programs, waste management, class duties, and recycling projects. The main challenges faced include limited facilities, lack of active participation from some school members, and difficulty in maintaining program consistency. Strategies applied include regular coordination, periodic evaluation, educational approaches for younger students, parental involvement, reward and sanction systems, and the formation of student environmental cadres.The Adiwiyata program management at SD Negeri Magelang 6 effectively fosters students’ responsibility toward the environment. This program serves as a model of best practices for character education based on environmental awareness in elementary schools.